Anti-fibrotic effect of extracellular vesicles derived from tea leaves in hepatic stellate cells and liver fibrosis mice - Gong, Qianyuan; Zeng, Zhaoyu; Jiang, Tao; Bai, Xue; Pu, Chunlan; Hao, Yaying; Guo, Yuanbiao (Frontiers in Nutrition, 2022)
Background: Activation of hepatic stellate cells (HSCs) is essential for the pathogenesis of liver fibrosis, there is no effective drug used to prevent or reverse the fibrotic process. Methods: With human hepatic stellate cell line LX-2 and mouse model of CCl4-induced liver fibrosis, we investigated the anti-fibrotic effect to liver fibrosis of extracellular vesicles (EVs) extracted from tea leaves through cytological tests such as cell proliferation, cell migration, and cell fibrotic marker. Results: It was found that tea-derived EVs (TEVs) inhibited HSCs activation. In CCl4-induced liver fibrosis model, TEVs treatment can significantly improve the pathological changes of liver tissue, inhibit collagen deposition, reduce the number of lipid droplets in liver tissue, and reduce serum AST and ALT levels. In addition, TEVs inhibited TGF-β1 signaling and miR-44 in TEVs had the potential inhibitory effect on liver fibrosis. Conclusions: Taken together, our work suggesting that TEVs are novel therapeutic potential for liver fibrosis.